Optimization of Vehicle Routing Using Genetic Algorithm in Package Delivery Distribution: (Case Study at PT XYZ Samarinda Region) - Def Afuww Wildan Everest; Rachmawati W (Jurnal Media Infotama, 2025)
In recent years, companies in Indonesia and around the world have focused on logistics costs to achieve efficiency in the supply chain. This research focuses on vehicle route optimization in the package distribution process at PT XYZ in the Samarinda region, taking into account service time, demand, and vehicle capacity. The problem addressed is the delay in land transportation that causes inefficiency in package distribution, which is solved using a genetic algorithm to generate the minimum travel distance and the shortest route, in order to minimize sustainable package distribution costs. The research results show optimization of the number of fleets and routes, as well as a significant reduction in total travel distance and total distribution costs. Keyword: Supply Chain, Logistics, Vehicles, Transportation, Optimization, Linear Programming, Genetic Algorithm, Hyrbid, Supply Chain, Shortest Route, Vehicle Routing Problem.